Analisis Identifikasi Pariwisata Andalan, Pengembangan dan Potensial Dengan Metode SWOT - natalia artha malau; teguh pamuji tri nur H (Universitas Negeri Surabaya, 2022)
Abstract This study aims to see the development of tourism in Demak Regency-Central Java by using tourism methods that are Mainstay, Development and Potential. Where the method by giving a value / score to the existing condition variables of each tourism object that has been determined based on predetermined criteria. The criteria are tourist attraction, supporting facilities, location and accessibility, market, management and impact on the surrounding to area, competitiveness of tourism objects. The calculation results obtained from 22 tourism objects in Demak Regency, which are included in the leading category (mainstay) a number of 3 locations are the Great Mosque of Demak, the Museum of the Great Mosque of Demak, and Gravestone of Sunan Kalijaga (Kadilangu). Keywords : Mainstay Tourism, Development Tourism, Potential Tourism., SWOT